The influence of destination image on tourist at Kuta Beach, Bali - Farah Ansetti; Fitri Widjaja (Faculty of Business and Economics, University of Surabaya, 2025)
This study aims to examine the effect of destination image on tourist loyalty at Kuta Beach, Bali. The dependent variable used is Tourist Loyalty, while the independent variables used are Destination Image, Perceived Value, Perceived Service Quality, Attitude to Visiting Behavior, and Tourist Satisfaction. This study uses primary data sources by distributing online questionnaires, with a total sample of 145 respondents aged 17 years and over who have visited Kuta Beach, Bali, in the last 3 years. This study uses a research method using SmartPLS software. The results of this study show that attitude toward visiting behavior has a positive effect on tourist loyalty. Destination image and perceived service quality significantly affect tourist satisfaction. Perceived service quality and perceived value significantly affect the destination image. Destination image and perceived service quality have no significant effect on attitude toward visiting behavior. Tourist satisfaction significantly affects the attitude toward visiting behavior.